A comprehensive analysis of SNPs and CNVs identifies novel markers associated with disease outcomes in colorectal cancer. Issue 12 (5th August 2021) - Yu, Yajun; Werdyani, Salem; Carey, Megan; Parfrey, Patrick; Yilmaz, Yildiz E.; Savas, Sevtap
Abstract : We aimed to examine the associations of a genome‐wide set of single nucleotide polymorphisms (SNPs) and 254 copy number variations (CNVs) and/or insertion/deletions (INDELs) with clinical outcomes in colorectal cancer patients ( n = 505). We also aimed to investigate whether their associations changed (e.g., appeared, diminished) over time. Multivariable Cox proportional hazards and piece‐wise Cox regression models were used to examine the associations. The Cancer Genome Atlas (TCGA) datasets were used for replication purposes and to examine the gene expression differences between tumor and nontumor tissue samples. A common SNP ( WBP11‐ rs7314075) was associated with disease‐specific survival with P ‐value of 3.2 × 10 −8 . Association of this region with disease‐specific survival was also detected in the TCGA patient cohort. Two expression quantitative trait loci (eQTLs) were identified in this locus that were implicated in the regulation of ERP27 expression. Interestingly, expression levels of ERP27 and WBP11 were significantly different between colorectal tumors and nontumor tissues. Three SNPs predicted the risk of recurrent disease only after 5 years postdiagnosis. Overall, our study identified novel variants, one of which also showed an association in the TCGA dataset, but no CNVs/INDELs, that associated with outcomes in colorectal cancer. Three SNPs were candidate predictors of long‐term recurrence/metastasis risk. Abstract : Stratifying patients with colorectal cancer (CRC) into high and low outcome risk groups is important for informing treatment and follow‐up strategies. Here, we examined the associations of a genome‐wide set of single nucleotide polymorphisms (SNPs) and a set of copy number variations and indels with clinical outcomes in patients with CRC. We showed that CRC patients can be distinguished for their risk of death from this disease based on their genotypes of a SNP in the WBP11 gene.